1996
DOI: 10.1093/jnci/88.16.1118
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Sex Hormone Levels and Risk of Prostate Cancer

Abstract: High levels of circulating testosterone and low levels of SHBG-both within normal endogenous ranges-are associated with increased risks of prostate cancer. Low levels of circulating estradiol may represent an additional risk factor. Circulating levels of DHT and AAG do not appear to be strongly related to prostate cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
449
6
19

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 691 publications
(511 citation statements)
references
References 29 publications
26
449
6
19
Order By: Relevance
“…25,26 Furthermore, accumulating evidence suggests that prostate carcinogenesis by alcohol is mediated through increased estrogens and decreased androgens and sex hormone-biding globulin. [27][28][29][30][31][32] Results regarding the effect of smoking on prostate cancer have been inconsistent. Our present results showed that smoking decreased the risk of prostate cancer in total subjects, but that this negative association might have been impaired in subjects whose cancer was detected by subjective symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Furthermore, accumulating evidence suggests that prostate carcinogenesis by alcohol is mediated through increased estrogens and decreased androgens and sex hormone-biding globulin. [27][28][29][30][31][32] Results regarding the effect of smoking on prostate cancer have been inconsistent. Our present results showed that smoking decreased the risk of prostate cancer in total subjects, but that this negative association might have been impaired in subjects whose cancer was detected by subjective symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The possible effects of physiologic sex steroids have been demonstrated in the progression of breast and prostate cancers. [33][34][35][36][37] Physiologic steroid hormones can also affect systemic organs. Thus, the results of the current study indicate that physiologic GCs may also play a role in the inhibition of tumorigenesis of thymic epithelial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…First, high levels of bioavailable testosterone has been associated with increased risk of prostate cancer (Gann et al, 1996;. Several studies have reported lower levels of free testosterone (Tikkanen et al, 1998;Tymchuk et al, 2001) in athletically trained men relative to untrained men and immediately after exercise (Nindl et al, 2001) as well as increased levels of sex hormone binding globuline (SHBG) immediately after exercise in older men (Zmuda et al, 1996) and after an exercise programme (Caballero et al, 1992;Tymchuk et al, 1998).…”
Section: Epidemiologymentioning
confidence: 99%